Low-carbon low-magnetic concrete and preparation method thereof
Patent Information
- Application Number
- CN202610996888.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]目前,已有一定低磁混凝土的报道,如:专利CN106630804B公开了一种低碳低磁混凝土,该方案需使用特制低磁水泥,并严格限定熟料中C3S、C2S、C4AF、C3A的矿物组成比例与立升重指标,技术推广难度大,成本高,且仍以硅酸盐水泥熟料为主体,碳排放高;专利申请CN120794471A公开的低磁混凝土中,需要提前对粗骨料进行氧化铝改性,随后经两次铝盐浸泡、烘干、高温烧结等多道工序,同时需额外制备氧化石墨烯接枝改性玄武岩纤维,工序繁琐,难以满足工程建设的大批量供货需求
1)硼硅玻璃纳米微珠在硫铝酸盐水泥的碱性水化环境中,会缓慢溶出硼酸盐与活性硅,一方面可与磁性矿物表面的铁离子发生反应,生成非磁性铁硼硅酸盐玻璃相,另一方面纳米级微珠在填充浆体密实性的同时还可有效促进体系钙矾石生成,阻断泌水与渗水通道,促使混凝土的工作性、抗渗性、抗裂性与耐久性能等得到同步提升。
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to a low-carbon, low-magnetic concrete and its preparation method. Background Technology
[0002] With the rapid development of research in extremely weak magnetic fields and zero-magnetic medical diagnosis and treatment, the spatial remanence of building structural materials typically needs to be controlled below 10 nT, far lower than the magnetic field level of conventional building environments. Concrete, as the most widely used building structural material, inevitably contains ferromagnetic mineral impurities such as magnetite and maghematite in its raw materials, including cement and aggregates. The remanence of the finished product is generally in the range of several thousand nT, which cannot meet the construction requirements of the aforementioned special scenarios. At the same time, the pressure to reduce carbon emissions in the building materials industry is increasing daily. Developing concrete materials that combine low magnetic properties with low carbon emissions has significant engineering value and environmental significance.
[0003] Currently, there have been some reports on low-magnetic concrete. For example, patent CN106630804B discloses a low-carbon, low-magnetic concrete. This solution requires the use of specially formulated low-magnetic cement and strictly limits the mineral composition ratio and liter weight index of C3S, C2S, C4AF, and C3A in the clinker. The technology is difficult to promote and has high costs. Moreover, it still mainly uses silicate cement clinker, resulting in high carbon emissions. In the low-magnetic concrete disclosed in patent application CN120794471A, the coarse aggregate needs to be modified with alumina in advance, followed by multiple processes such as two aluminum salt soakings, drying, and high-temperature sintering. At the same time, it is necessary to additionally prepare graphene oxide grafted modified basalt fibers. The process is complicated and difficult to meet the large-scale supply requirements of engineering construction.
[0004] Existing low-magnetic concrete technologies generally suffer from low solid waste utilization rates, high costs and energy consumption, high carbon emissions, or reliance on complex pretreatment processes, resulting in poor scalability. Therefore, there is an urgent need to provide a low-magnetic concrete with both stable low-magnetic properties and low-carbon environmental advantages, along with an efficient and simple preparation method, to meet the industry's pressing demand for high-performance green building materials. Summary of the Invention
[0005] The main objective of this invention is to provide a low-carbon, low-magnetic concrete and its preparation method, which achieves stable low magnetic properties while also possessing excellent mechanical and durability properties. Furthermore, it is easy to operate, has low cost, and is suitable for widespread application.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A low-carbon, low-magnetic concrete comprises the following raw materials by weight: 90-110 parts of ultra-low iron sulfoaluminate cement, 60-90 parts of composite activated lithium slag, 40-60 parts of coal gangue powder, 70-110 parts of waste paper pulp ash, 3-6 parts of borosilicate glass nanospheres, 850-950 parts of quartz sand, 1000-1100 parts of crushed quartz stone, 150-160 parts of water, and 4-6 parts of admixtures; wherein the composite activated lithium slag is obtained by mechanically and by sodium sulfate composite activation and magnetic field dry separation and purification of lithium mica tailings.
[0007] In the above scheme, the ultra-low iron sulfoaluminate cement is a rapid-hardening sulfoaluminate cement of grade 42.5 or higher, and its clinker contains anhydrous calcium sulfoaluminate (C4A3). The mass fraction of Fe2O3 is ≥55%, the mass fraction of Fe2O3 is ≤0.3%, and the specific surface area is controlled between 350 and 400 m². 2 / kg, initial setting time ≥25min, final setting time ≤180min.
[0008] In the above scheme, the composite activated lithium slag is obtained by mechanical and chemical composite activation and magnetic field dry separation and purification of lithium mica tailings. Its Fe2O3 mass fraction is <0.2% (iron element exists in a uniformly dispersed bound state, without strongly magnetic crystalline iron mineral clusters, which is the core carrier of lithium slag pozzolanic activity, and can undergo synergistic hydration with borosilicate glass nanospheres and waste paper pulp ash in the system, and has both activation and demagnetization enhancement effects), and its specific surface area is 400~450m². 2 / kg, 28d activity index ≥75%, glass phase (aluminosilicate based) content ≥60%; during the activation process, 0.5~1.0wt% of anhydrous sodium sulfate (as a percentage of the amount used in lithium mica lithium extraction tailings) is introduced as an activation aid to simultaneously remove native ferromagnetic impurities.
[0009] Furthermore, the specific preparation process of the composite activated lithium slag is as follows: (1) Dry the lithium extraction tailings from lepidolite (105~110℃) to a moisture content of ≤1.0%, and after crushing and screening, obtain homogenized powder with a particle size of ≤5mm. Remove large ferromagnetic impurities mixed in the raw material in advance. (2) The pretreated lithium slag powder is ball-milled with anhydrous sodium sulfate activator accounting for 0.5~1.0% of the dry basis of the lithium slag powder, and the grinding time is controlled at 40~60min (the ball milling rate is 90~150r / min) to obtain the initially activated lithium slag.
[0010] (3) The initial activated lithium slag is fed into a dry high gradient magnetic separator for deep impurity removal. The separation magnetic field strength is controlled at 1.2~1.6T, the powder feeding speed is 0.8~1.2t / h, and the magnetic separation time is 5~10min to obtain the composite activated lithium slag product.
[0011] This invention utilizes an integrated mechanical-chemical activation and dry magnetic separation process to effectively activate lithium slag volcanic ash while removing native ferromagnetic impurities. Residual bound iron enters the CASH gel lattice in a substituted form (being solidified and losing its migration and aggregation ability), and serves as a heterogeneous nucleation site to accelerate the precipitation of hydration products, achieving a positive synergy between demagnetization and enhancement. Simultaneously, it forms an "adsorption-anchoring" dual-effect mechanism with the porous carbonaceous components of waste paper pulp ash, further blocking the migration and crystallization pathways of iron ions.
[0012] In the above scheme, the coal gangue powder is coal-based kaolinite coal gangue with Fe2O3 mass fraction ≤0.5% and loss on ignition ≤3.0%; primary ferromagnetic impurities need to be removed.
[0013] In the above scheme, the waste paper pulp ash is obtained by calcining waste paper pulping residue from the papermaking industry at a low temperature of 600~700℃ for 1~1.5h and then grinding and homogenizing; wherein, the Fe2O3 mass fraction is ≤0.8%, the loss on ignition is ≤8.0%, and the specific surface area is 350~400m². 2 / kg, the total mass fraction of SiO2 and Al2O3 is ≥60%, and the content of residual porous carbonaceous components is 8~15wt%.
[0014] In the above scheme, the average particle size of the borosilicate glass nanospheres is 300~800nm, the Fe2O3 mass fraction is ≤0.1%, and the sphericity is ≥95%.
[0015] In the above scheme, the active quartz sand has a SiO2 content ≥98%, an Fe2O3 content ≤0.03%, a fineness modulus between 2.3 and 3.0, a mud content ≤0.5%, and a mud lump content ≤0.2%.
[0016] In the above scheme, the quartz crushed stone has an Fe2O3 content ≤ 1.0%, a needle-like / flaky content ≤ 5%, a crushing value ≤ 10%, and a water absorption rate ≤ 1.0%. In the above scheme, the admixture is a water-reducing agent, preferably a high-performance polycarboxylate water-reducing agent with a water reduction rate ≥30% and a solid content ≥20%.
[0017] The above-mentioned method for preparing low-magnetic concrete includes the following steps: S1 Weigh each raw material according to the weight ratio. First, place the weighed quartz sand and quartz crushed stone in the aggregate bin. Spray an additional 10-15% (not included in the total water volume of the formula) of clean water for pre-wetting treatment. Let it stand (10-15 minutes) to form a stable water film on the surface of the aggregate, reducing the workability fluctuations caused by the aggregate absorbing water during the mixing process. S2 weighs out ultra-low iron sulfoaluminate cement, composite activated lithium slag, coal gangue powder, waste paper pulp ash, borosilicate glass nanospheres, a portion of the mixing water, and all the additives, and puts them into a forced mixer for gradient mixing. The specific steps include: first, dry mixing at 30~40 r / min for 30~60s to ensure that the powder components are fully mixed and the nanospheres are evenly dispersed in the cementitious system; then, adding 50~60% of the total water volume of mixing water and all the additives, and then mixing at 40~50 r / min (higher than the previous step) for 60~90s to obtain a uniformly dispersed cementitious slurry. S3 adds pre-wetted quartz sand and crushed quartz to the above-mentioned cementitious slurry, along with the remaining mixing water, and increases the speed to 80~120r / min and mixes for 120~150s until the slurry is homogeneous and the aggregate surface is completely coated, thus obtaining freshly mixed low-carbon and low-magnetic concrete.
[0018] Furthermore, the obtained freshly mixed low-carbon and low-magnetic concrete was poured into the mold and compacted by vibration. After the surface was covered with a film for moisturizing and curing for 24 hours, it was demolded and placed in a standard curing environment (temperature 20±2℃, relative humidity ≥95%) for curing until the specified age. Throughout the curing process, contact with strong magnetic equipment and ferromagnetic components was avoided to prevent the concrete from being magnetized by the external magnetic field, thus obtaining low-carbon and low-magnetic concrete specimens.
[0019] The low-carbon, low-magnetic concrete prepared according to the above scheme has an initial slump of 180~220mm in the freshly mixed state, a slump time of <4s, good workability, and meets the requirements of conventional pumping construction. After hardening (test specimens), the compressive strength after 28 days is ≥35MPa, the flexural strength is ≥4.5MPa, the early strength development is rapid, and the crack resistance grade reaches above Grade III. The remanent magnetic strength of the concrete body after 28 days is ≤5nT, and the long-term stability of magnetic properties is excellent. At the same time, the solid waste replacement rate of the cementitious material system is ≥60%, and the carbon emissions are reduced by more than 40% compared with ordinary silicate concrete of the same strength grade. It has multiple advantages of low magnetism, high strength, durability, and low carbon emissions.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) In the alkaline hydration environment of sulfoaluminate cement, borosilicate glass nanospheres slowly dissolve borate and active silicon. On the one hand, they can react with iron ions on the surface of magnetic minerals to generate a non-magnetic iron borosilicate glass phase. On the other hand, while filling the density of the slurry, the nanospheres can also effectively promote the formation of ettringite in the system, block the bleeding and seepage channels, and promote the simultaneous improvement of the workability, impermeability, crack resistance and durability of concrete.
[0021] 2) The combined effect of borosilicate glass nanospheres and waste paper pulp ash can effectively improve the overall performance of concrete. The active borosilicate components dissolved from the glass nanospheres can undergo a synergistic hydration reaction with the endogenous alkali and aluminosilicate components of waste paper pulp ash to generate a large number of aluminoborosilicates containing coordination vacancies. This further helps to capture free iron ions in the liquid phase and effectively seal them in the gel skeleton, promoting the improvement of matrix density and later strength, and improving the problems of low early hydration activity and large volume shrinkage of solid waste.
[0022] 3) Waste paper pulp ash can effectively reduce the magnetism introduced by lithium slag in the system; the porous carbonaceous components remaining in the waste paper pulp ash have a certain physical adsorption and complexation effect on the soluble iron ions introduced by lithium slag in the system, anchoring the ferric hydroxide colloid and soluble iron components in the pulp, preventing the migration and aggregation of iron elements to form strongly magnetic magnetite, which helps to further reduce the iron ion concentration in the liquid phase; the anchored highly dispersed bound iron can enter the CASH gel lattice through isomorphous substitution, reducing the activation energy of the aluminosilicate polymerization reaction, and at the same time, it acts as a heterogeneous nucleation site to accelerate the precipitation of hydration products, synergistically promoting the improvement of the hydration degree of the gelation system, and achieving a positive synergy of demagnetization and enhancement.
[0023] 4) The special mixing process designed in this invention can promote the uniform dispersion of each component, avoid fluctuations in the magnetic properties of concrete caused by the enrichment of local ferromagnetic impurities, and, together with the external magnetic field avoidance measures throughout the curing process, further ensure the batch stability and long-term consistency of the magnetic properties of the finished product. Detailed Implementation
[0024] The present invention will be further described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] In the following examples, anhydrous calcium sulfoaluminate (C4A3) in ultra-low iron sulfoaluminate cement clinker The mass fraction of Fe2O3 is 61.3%, the mass fraction of Fe2O3 is 0.22%, and the specific surface area is 366 m². 2 / kg, initial setting time is 35min, final setting time is 162min.
[0026] The composite activated lithium slag used was obtained from lithium mica extraction tailings through mechanical and chemical composite activation and magnetic field dry separation and purification. Its Fe2O3 mass fraction was 0.16%, and its specific surface area was 429 m². 2 / kg, with an activity index of 84% and a glass phase content of 67.2% after 28 days; the specific preparation method includes the following steps: (1) The lithium extraction tailings of lepidolite were dried in an environment of 110℃ and the moisture content was measured to be 0.4%. After crushing and screening, homogenized powder with a particle size ≤5mm was obtained. Large ferromagnetic impurities mixed in the raw material were screened out in advance. (2) The pretreated lithium slag powder and anhydrous sodium sulfate activator accounting for 0.8% of the dry weight of lithium slag were fed into a dry ball mill and the grinding time was controlled at 50 min (the ball milling rate was 120 r / min) to obtain the initially activated lithium slag.
[0027] (3) The initial activated lithium slag is fed into a dry high gradient magnetic separator for deep impurity removal. The magnetic field strength is controlled at 1.4T, the powder feeding speed is 1.0t / h, and the magnetic separation is carried out for 6min to finally obtain the composite activated lithium slag product.
[0028] The coal gangue powder used is coal-series kaolinite coal gangue with a Fe2O3 mass fraction of 0.38% and a loss on ignition of 2.4%.
[0029] The waste paper pulp ash used contained 0.43% Fe2O3 by mass, 6.1% loss on ignition, and 369 m² of specific surface area. 2 / kg, the total mass fraction of SiO2 and Al2O3 is 62.7%, and the proportion of residual porous carbonaceous components is 10.2%; the waste paper pulp ash residue of the papermaking industry is obtained by calcining at 680℃ for 1h and grinding and homogenizing.
[0030] The borosilicate glass nanospheres used have an average particle size of 516 nm, an Fe2O3 mass fraction of 0.06%, and a sphericity of 97%.
[0031] The quartz sand used comes from Changde, Hunan Province. It has an active SiO2 content of 98.6%, an Fe2O3 content of 0.008%, a fineness modulus of 2.6, a mud content of ≤0.5%, and a mud lump content of ≤0.2%.
[0032] The quartz crushed stone used was taken from Daye, with an Fe2O3 content of 0.13%, a needle-like and flaky content of 4.6%, a crushing index of 7.2%, and a water absorption rate of 0.3%.
[0033] Before using the quartz sand and crushed quartz, place the quartz sand and crushed quartz in the aggregate bin and spray an additional 12% (not included in the total water volume of the formula) of clean water for pre-wetting treatment. Let it stand (10 minutes) to obtain pre-wetted quartz sand and crushed quartz.
[0034] The admixture used is a high-performance polycarboxylate superplasticizer provided by China Construction Western Construction New Materials Technology Co., Ltd., with a water reduction rate of 33.4% and a solid content of 29.6%.
[0035] Example 1 A low-magnetic concrete, the preparation method of which includes the following steps: 1) Raw material weighing, the raw materials and their weight percentages are as follows: 110 parts of ultra-low iron sulfoaluminate cement, 60 parts of composite activated lithium slag, 60 parts of coal gangue powder, 70 parts of waste paper pulp ash, 3 parts of borosilicate glass nanospheres, 900 parts of quartz sand, 1050 parts of crushed quartz stone, 155 parts of water, and 5 parts of high-performance polycarboxylate superplasticizer. 2) First, weigh the ultra-low iron sulfoaluminate cement, composite activated lithium slag, coal gangue powder, waste paper pulp ash, and borosilicate glass nanospheres into a forced mixer. First, dry mix at 35 r / min for 60 s. Then, add 55% of the total water volume of mixing water and the full amount of high-performance polycarboxylate superplasticizer. Mix at 45 r / min for 90 s to obtain a uniformly dispersed cementitious slurry. 3) Add pre-wetted quartz sand and crushed quartz to the above cementitious slurry, and add all the remaining mixing water at the same time. Increase the speed to 100 r / min and mix for 120 s to obtain freshly mixed low-carbon and low-magnetic concrete. 4) After the freshly mixed concrete is poured into the mold, it is vibrated to make it dense. After the surface is covered with a film to keep it moist for 24 hours, it is demolded and placed in a standard curing environment to cure until the specified age. Throughout the curing process, contact with strong magnetic equipment and ferromagnetic components should be avoided to prevent the concrete from being magnetized by the external magnetic field, so as to obtain low-carbon and low-magnetic concrete specimens.
[0036] Example 2 A low-magnetic concrete is prepared in a manner similar to that of Example 1, except that it contains: 100 parts of ultra-low iron sulfoaluminate cement, 75 parts of composite activated lithium slag, 50 parts of coal gangue powder, 90 parts of waste paper pulp ash, 4.5 parts of borosilicate glass nanospheres, 900 parts of quartz sand, 1050 parts of crushed quartz stone, 155 parts of water, and 5 parts of high-performance polycarboxylate superplasticizer.
[0037] Example 3 A low-magnetic concrete is prepared in a manner similar to that of Example 1, except that it contains: 90 parts of ultra-low iron sulfoaluminate cement, 90 parts of composite activated lithium slag, 40 parts of coal gangue powder, 110 parts of waste paper pulp ash, 6 parts of borosilicate glass nanospheres, 900 parts of quartz sand, 1050 parts of crushed quartz stone, 155 parts of water, and 5 parts of high-performance polycarboxylate superplasticizer.
[0038] Comparative Example 1 A low-magnetic concrete is prepared in a manner largely the same as in Example 1, except that ordinary microspheres are used instead of the borosilicate glass nanospheres described in this invention. The ordinary microspheres are conventional fly ash microspheres with an average particle size of 34.6 μm. They contain no boron and cannot dissolve borate and active silicon functional components in an alkaline hydration environment, thus only having a simple physical filling effect.
[0039] Comparative Example 2 A low-magnetic concrete is prepared in a manner similar to that of Example 1, except that: no waste paper pulp ash is added, but instead an equal mass of coal gangue powder is used, keeping the total mass of the cementitious material constant.
[0040] Comparative Example 3 A low-magnetic concrete is prepared in a manner similar to that of Example 1, except that ultra-low iron sulfoaluminate cement is replaced with 42.5 grade low-iron white silicate cement of equal mass.
[0041] Comparative Example 4 A low-magnetic concrete is prepared in a manner similar to that of Example 1, except that the specific preparation steps of the activated lithium slag are as follows: after drying and crushing the lithium extraction tailings from lepidolite, it is first separately fed into a dry ball mill for 50 minutes (at a rate of 120 r / min); then anhydrous sodium sulfate, accounting for 0.8% of the dry weight of the lithium slag, is added and mixed for 10 minutes; subsequently, it is fed into a dry magnetic separator and separated under a magnetic field strength of 1.4T.
[0042] Comparative Example 5 A low-magnetic concrete is prepared using a method largely the same as in Example 1, except that a conventional one-time feeding and mixing process is employed. The specific steps are as follows: all raw materials are fed into the mixer at once and continuously mixed at 80 r / min for 180 s. The remaining curing conditions are the same as in Example 1. The concrete obtained in Examples 1-3 and Comparative Examples 1-5 were tested for initial slump, collapse time, 28-day remanent magnetic strength, 7-day and 28-day compressive strength, etc. The remanent magnetic strength was measured by a high-precision fluxgate magnetometer. The specific test results are shown in Table 1 below.
[0043] Table 1. Performance test results of concrete obtained in Examples 1-3 and Comparative Examples 1-5
[0044] The above results show that the present invention can effectively control the final remanent magnetization of concrete to within 5 nT, and further improve the workability and mechanical properties of solid waste low magnetic concrete.
[0045] This invention is not limited to the embodiments described above. Those skilled in the art can make various improvements and modifications without departing from the principles of this invention, and these improvements and modifications are also considered within the scope of protection of this invention. Contents not described in detail in this specification are prior art known to those skilled in the art.
Claims
1. A low-carbon, low-magnetic concrete, characterized in that, The raw materials, by weight, include: 90-110 parts of ultra-low iron sulfoaluminate cement, 60-90 parts of composite activated lithium slag, 40-60 parts of coal gangue powder, 70-110 parts of waste paper pulp ash, 3-6 parts of borosilicate glass nanospheres, 850-950 parts of quartz sand, 1000-1100 parts of crushed quartz, 150-160 parts of water, and 4-6 parts of additives; the composite activated lithium slag is obtained by mechanically and by sodium sulfate composite activation and magnetic field dry separation and purification of lithium mica tailings.
2. The low-carbon, low-magnetic concrete according to claim 1, characterized in that, The composite activated lithium slag contains Fe2O3 mass fraction <0.2% and a specific surface area of 400~450 m². 2 / kg, 28d activity index ≥75%, glass phase content ≥60%.
3. The low-carbon, low-magnetic concrete according to claim 1, characterized in that, The specific preparation process of the composite activated lithium slag is as follows: (1) The lithium extraction tailings from lepidolite are dried to a moisture content of ≤1.0%, and then crushed and screened to obtain homogenized powder with a particle size of ≤5mm; (2) The pretreated lithium slag powder is ball-milled with anhydrous sodium sulfate activator accounting for 0.5~1.0% of the dry basis of the lithium slag powder to obtain initially activated lithium slag; (3) The initially activated lithium slag is subjected to magnetic separation to obtain the composite activated lithium slag.
4. The low-carbon, low-magnetic concrete according to claim 1, characterized in that, The ultra-low iron sulfoaluminate cement is a rapid-hardening sulfoaluminate cement of grade 42.5 or higher, with anhydrous calcium sulfoaluminate mass fraction ≥55%, Fe2O3 mass fraction ≤0.3%, and a specific surface area of 350~400 m². 2 / kg; the coal gangue powder is coal-based kaolinite coal gangue, with Fe2O3 mass fraction ≤0.5% and loss on ignition ≤3.0%.
5. The low-carbon, low-magnetic concrete according to claim 1, characterized in that, The waste paper pulp ash is obtained by calcining waste paper pulping residue from the papermaking industry at a low temperature of 600~700℃ for 1~1.5h, followed by grinding and homogenization; wherein, the Fe2O3 mass fraction is ≤0.8%, the loss on ignition is ≤8.0%, and the specific surface area is 350~400m². 2 / kg, the total mass fraction of SiO2 and Al2O3 is ≥60%, and the content of residual porous carbonaceous components is 8~15wt%.
6. The low-carbon, low-magnetic concrete according to claim 1, characterized in that, The borosilicate glass nanospheres have an average particle size of 300~800nm, an Fe2O3 mass fraction of ≤0.1%, and a sphericity of ≥95%.
7. The low-carbon, low-magnetic concrete according to claim 1, characterized in that, The quartz sand contains ≥98% active SiO2, ≤0.03% Fe2O3, and has a fineness modulus of 2.3~3.0; the crushed quartz contains ≤1.0% Fe2O3, ≤5% needle-like and flaky content, ≤10% crushing value, and ≤1.0% water absorption.
8. The low-carbon, low-magnetic concrete according to claim 1, characterized in that, The admixture is a water-reducing agent with a water reduction rate of ≥30% and a solid content of ≥20%.
9. The method for preparing low-carbon, low-magnetic concrete according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1 Weigh each raw material according to the weight ratio, and first pre-wet the weighed quartz sand and quartz crushed stone. S2 is added with weighed ultra-low iron sulfoaluminate cement, composite activated lithium slag, coal gangue powder, waste paper pulp ash, borosilicate glass nanospheres, a portion of mixing water and all of the additives, and then subjected to gradient mixing to obtain a uniformly dispersed gel slurry. S3 adds pre-wetted quartz sand and crushed quartz to the above-mentioned cementitious slurry, along with the remaining mixing water, and mixes at high speed until homogeneous to obtain freshly mixed low-carbon, low-magnetic concrete.
10. The preparation method according to claim 9, characterized in that, The gradient mixing step described in S2 includes: first, dry mixing at a speed of 30-40 r / min for 30-60 seconds; then adding 50-60% of the total water volume of mixing water and all the additives used, and then mixing at a speed of 40-50 r / min for 60-90 seconds; The high-speed stirring step described in S3 is: stirring at a rate of 80~120r / min for 120~150s.
Citation Information
Patent Citations
A type of low-magnetic concrete
CN106630804B
Low-magnetism concrete
CN120794471A